Empowerment Coffee Farmers in Kemiri Village Through Actors Theory Based on Pentahelix Model - Kamillaeni Jamillah; Yossy Eka Pradita; Sri Wahyu Lelly Hana Setyanti (Jambura Equilibrium Journal, 2022)
The purpose of this study was to analyze the application of coffee farmer community empowerment through ACTORS theory based on the Pentahelix model as economic optimization of Kemiri Village, Panti District. Jember Regency is famous for its natural wealth, one of which is coffee plantations scattered throughout the region. Panti District is one of the coffee-producing areas and is included in the top 5 coffee producers with a potential harvest area of 149.70 with total coffee production in 2020 of 121.95 quintals (BPS Jember, 2021). One of the villages that have the potential for coffee is Kemiri Village. However, the existing potential has not been able to improve the standard of living of the community, especially coffee farmers (observation results, 2022). This problem can certainly be overcome and has relevance through ACTORS Theory and Pentahelix models which can be implemented for Kemiri Village coffee farmers. This research was conducted using a qualitative type with purposive and snowball sampling. The primary data was obtained through interviews and direct observation of the object of research. Secondary data is indirect data obtained from publications, documentation, journals. Through this research, it is hoped that researchers will be able to analyze the application of community empowerment for coffee farmers to be able to support the economy of the local community.